ANALISA KESELARASAN SDGs DENGAN PROGRAM PEMBANGUNAN DESA SERESAM DI DESA SERESAM DI KABUPATEN INDRAGIRI HULU - Roberta Zulfhi Surya (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Ministry of National Development Planning launched Voluntary National Report to support SDGs acceleration achievement. Therefore, SDGs Secretariat of Riau Province to do SDGs best practices survey to 12 district/city that facilitated by Development Plannig Agency at 12 district/city. This research was condusted by the survey and desk review method. The survey was conducted to collect data and information. Analysis result of alignment between national SDGs indicators and the Village Development Program conduct with desk review method. Base on analysis, Seresam village have successful to implementing SDGs at village level.